2019
DOI: 10.3389/fpsyt.2019.00784
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota in Bipolar Depression and Its Relationship to Brain Function: An Advanced Exploration

Abstract: The mechanism of bipolar disorder is unclear. Growing evidence indicates that gut microbiota plays a pivotal role in mental disorders. This study aimed to find out changes in the gut microbiota in bipolar depression (BD) subjects following treatment with quetiapine and evaluate their correlations with the brain and immune function. Totally 36 subjects with BD and 27 healthy controls (HCs) were recruited. The severity of depression was evaluated with the Montgomery-Asberg depression rating scale (MADRS). At bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 60 publications
(76 reference statements)
5
58
0
1
Order By: Relevance
“…Collinsella belongs to Coriobacteriia, which is reported to be associated with bipolar disorder and the related neural in ammation [27]. Eubacterium ventriosum group was negatively correlated with depression and anxiety levels in the current study, in consistency with previous reports of lower Eubacterium in UC and bipolar patients [28,29]. The increase of Bacteroidaceae in the patients with depression and anxiety is consistent with a previous study that mice monocolonized with Bacteroides fragilis, which could also produce GABA [20], display de cits in serum serotonin [19].…”
Section: Discussionsupporting
confidence: 91%
“…Collinsella belongs to Coriobacteriia, which is reported to be associated with bipolar disorder and the related neural in ammation [27]. Eubacterium ventriosum group was negatively correlated with depression and anxiety levels in the current study, in consistency with previous reports of lower Eubacterium in UC and bipolar patients [28,29]. The increase of Bacteroidaceae in the patients with depression and anxiety is consistent with a previous study that mice monocolonized with Bacteroides fragilis, which could also produce GABA [20], display de cits in serum serotonin [19].…”
Section: Discussionsupporting
confidence: 91%
“…A new concept of brain‐gut coefficient of balance (B‐G CB ), the ratio of oxygenated hemoglobin to B/E, was proposed. We found log 10 (B‐G CB ) was positively correlated with peripheral CD3 + T‐cell proportion 38 . These findings indicated the intrinsic balance of the MGB axis might be regulated by the immune pathway.…”
Section: Gut Microbiome and Bd In Human Studiesmentioning
confidence: 89%
“…and Enterobacteriaceae spp., was lower than that of the healthy controls. Based on these observations, it was suggested that the composition of the gut microbiota and its connectivity with brain function were altered in the BD group [ 76 ]. Table 3 summarizes the main characteristics of these trials.…”
Section: Microbiome Research In Psychiatric Disordersmentioning
confidence: 99%